Praying with the Desert Mothers - Kardong, Terrence 1936-2019 (2006)
The article reviews the book "Praying with the Desert Mothers," by Mary Forman.
Keywords: Christianity; Forman, Mary; Nonfiction; Praying With the Desert Mothers (Book); Rezension